2020
DOI: 10.1186/s12885-020-07052-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status according to the mini nutritional assessment (MNA)® as potential prognostic factor for health and treatment outcomes in patients with cancer – a systematic review

Abstract: Background Patients with cancer have an increased risk of malnutrition which is associated with poor outcome. The Mini Nutritional Assessment (MNA®) is often used in older patients with cancer but its relation to outcome is not known. Methods Four databases were systematically searched for studies relating MNA-results with any reported outcome. Two reviewers screened titles/abstracts and full-texts, extracted data and rated the risk of bias (RoB) independently. Results We included 56 studies which varied wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 123 publications
(209 reference statements)
3
31
1
1
Order By: Relevance
“… 45 Obviously, GNRI is a simple and objective tool for clinicians to screen patients readily based only on height, weight, and serum albumin levels. Its advantages would be more prominent than some questionnaires, such as subjective global assessment (SGA) 49 or Mini Nutritional Assessment (MNA), 50 which would be difficult to complete for elderly patients who had difficulties in communicating such as those with conscious disturbance or those who had been intubated.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Obviously, GNRI is a simple and objective tool for clinicians to screen patients readily based only on height, weight, and serum albumin levels. Its advantages would be more prominent than some questionnaires, such as subjective global assessment (SGA) 49 or Mini Nutritional Assessment (MNA), 50 which would be difficult to complete for elderly patients who had difficulties in communicating such as those with conscious disturbance or those who had been intubated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in elderly individuals, malnutrition is associated with time of re-admission to the hospital, infections, gait disturbances, falls, fractures, and delayed healing of wounds 10 . In a systematic review, it was stated that individuals with low MNA scores had longer hospital stays than those with high MNA scores 11 . Unlike these studies, some studies reported that no relationship was found between malnutrition and length of hospital stay 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…The GNRI can be easily acquired on the basis of the sex, height, weight, and serum albumin levels of patients. For polytrauma patients who have difficulties in communicating, such as those with conscious disturbance or those under intubation, the advantages of using the GNRI is that it would supersede traditional questionnaires, including the subjective global assessment (SGA) [ 50 ] or Mini Nutritional Assessment (MNA) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%